Screening of Lithium Substituted Ag-TiO2 Nanoparticle Coating for Antibiofilm Application - Pradhan L.; Hazra S.; Manna S.; Pal B.N.; Mukherjee S. (My University, 2025)
Bacterial infections and biofilm growth are common mishaps associated with medical devices, and they contribute significantly to ill health and mortality. Removal of bacterial deposition from these devices is a major challenge, resulting in an immediate necessity for developing antibacterial coatings on the surfaces of medical implants. In this context, we developed an innovative coating strategy that can operate at low temperatures (80 °C) and preserve the devices’ integrity and functionality. An innovative Ag-TiO2 based coating was developed by ion exchange between silver nitrate (AgNO3) and lithium titanate (Li4Ti5O12) on glass substrates for different periods, ranging from 10 to 60 min. The differently coated samples were tested for their antibacterial and antibiofilm efficacy. © 2024 American Chemical Society.